Instilling ethical behavior in organizations: A survey of Canadian companies - Lindsay, R. Murray (Journal of business ethics, 1996)
An organization's management control system can play an important role in influencing ethical behavior among employees. In this paper a theoretical framework of control is developed by linking various ethics related control mechanisms reported in the literature to the primary components of a management control system. In addition, the findings of a survey of the Financial Post's Top 1 000 Canadian industrial and service companies are reported. The survey investigated organizations' use of ethical codes of conduct, whistleblowing systems, ethics committees, judiciary boards, employee training in ethics, and ethics focused corporate governance and reward systems. The findings indicate that ethics related control mechanisms, particularly codes of conduct, are being used by a good number of organizations. However, closer analysis of the data suggests that many companies may only be paying lip service to the importance of promoting ethical behavior.